Sustainability accounting and management - Taylor, Julia (New York Willford press, 2020)
The subcategory of financial accounting which focuses on the disclosure of non-financial information about a firm's performance is known as sustainability accounting. It generally reports to external stakeholders, such as capital holders, creditors and other authorities. The activities which have a direct impact on society, environment and economic performance of an organization are represented by sustainability accounting. Corporate sustainability reporting and triple bottom line accounting are the two most widely used measurements in this discipline.
Keywords: Business and Management; Accounting and Finance; Management Business